THE EFFECTIVITY OF INTEGRATED UNDERGROUND INFRASTRUCTURE FOR JAKARTA FLOOD CONTROL - Segel Ginting; William M Putuhena (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Jakarta has very complex problems from flood to traffic jams. One solution that has been considered is the utilization of underground space called as Infrastruktur Terpadu Bawah Tanah abbreviated as ITBT (Jakarta Integrated Tunnel) which is used for flood control and toll road. ITBT proposed as flood control consists of two traces, namely ITBT-1 from Balekambang to Manggarai and ITBT-2 from Ulujami to Tanah Abang. The performance effectiveness of ITBT-1 and ITBT-2 as flood controls assessed based on mathematical model approach that simulates the characteristics of floods in Jakarta. is the performance is done by predicting how much ITBT can reduce flood inundation (flood risk). The results indicate insignificant reductions since floodwaters diversion carried out by both ITBT only reduce the puddle within the controlled area, and create another in other areas. Flood inundation reduction is still more effective if done by river improvement. ITBT-1 would be more effective if the trace is transferred into east flood canal (BKT) or sea through alignment under BKT, moreover if there is an inlet regulation to ITBT-1.